Method for preparing perovskite layer through two-step coating method, perovskite layer and photovoltaic module
Through the two-step coating method and the use of ammonium fluoride, the aerogel template is used to guide the growth of perovskite crystals, which solves the problem of poor crystallinity and uniformity of the perovskite layer and improves the photoelectric performance of solar cells.
Patent Information
- Application Number
- CN202411255308.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-17
AI Technical Summary
The current two-step method for preparing perovskite layers has poor crystallinity and uniformity, which leads to fluctuations in the performance of solar cells.
Using a two-step coating method, the combination of aerogel template and precursor solution is used to guide the growth of perovskite crystals through the pore structure of the aerogel template, and ammonium fluoride is added when preparing the precursor solution to promote the crystallization process and Improve interface characteristics.
The crystallinity and uniformity of the perovskite layer are improved, grain boundary defects and charge composite centers are reduced, photoelectric performance and charge transfer efficiency are improved, and the light absorption efficiency of the film is enhanced.
Smart Images

Figure CN119156095A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of perovskite photovoltaic cells, and in particular to a method for preparing a perovskite layer by a two-step coating method, a perovskite layer and a photovoltaic module. Background Art
[0002] Due to its high photoelectric conversion efficiency, low-cost manufacturing and good adjustability, perovskite materials can effectively absorb sunlight and generate electron-hole pairs at a relatively thin thickness. They also have excellent adjustability and can adjust their photoelectric performance according to different needs to meet diverse application scenarios. They have rapidly emerged in the field of photovoltaic devices and have significant application advantages.
[0003] The two-step method for preparing the perovskite layer is an important method in the preparation of perovskite solar cells. The method mainly includes two steps: first, a uniform PbI2 film is formed on the substrate by a solution method or a vacuum method; then, a solution containing an organic halide (such as methylamine iodine MAI or iodoformamidine FAI) is reacted with PbI2 by coating or immersion to form a perovskite film. This method helps to optimize the crystallinity and uniformity of the perovskite layer by controlling the film formation process step by step.
[0004] Although the two-step method helps to form high-quality perovskite films, in actual operation, the uniformity of the film is still difficult to fully control, and there are still challenges in crystallinity and stability, which may lead to fluctuations in the performance of solar cells. Summary of the invention
[0005] The embodiments of the present application provide a method for preparing a perovskite layer by a two-step coating method, a perovskite layer and a photovoltaic module, so as to solve the problem that the perovskite layer prepared by the two-step method in the related art has poor crystallinity and uniformity.
[0006] In a first aspect, a method for preparing a perovskite layer by a two-step coating method is provided, comprising the following steps:
[0007] S1. Providing aerogel template:
[0008] S101, mixing 99% ethyl silicate and anhydrous ethanol in a volume ratio of 1:5 to 1:10, adding deionized water and 1 mol / L hydrochloric acid solution, stirring evenly to obtain a sol, wherein the volume ratio of the ethyl silicate to the deionized water is 1:1 to 1:10, and the volume ratio of the hydrochloric acid solution to the ethyl silicate is 1:100;
[0009] S102, placing the sol in a sealed container, stirring at 50-65° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0010] S103, placing the wet gel in a freezing device, starting to freeze at 25°C, cooling at a constant rate to -80°C, and keeping for 5 to 30 minutes to obtain a frozen gel, with a freezing rate of 0.5 to 5°C / min;
[0011] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature is uniformly raised from -60 to -50 °C to 20 °C, and the heating process is maintained for 3 to 8 hours to obtain an aerogel template;
[0012] S2. Prepare a precursor solution: mix 0.1 mol / L lead acetate and 0.1 mol / L potassium iodide in a volume ratio of 1:3 to 1:5, and add ammonium fluoride to obtain a precursor solution, wherein the molar ratio of ammonium fluoride to lead acetate is 1:20 to 1:50;
[0013] S3, preparing an aerogel-precursor solution: dispersing the aerogel template into the precursor solution at a mass volume ratio of 1:50 to 1:80, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0014] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto a substrate to form a precursor film;
[0015] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 50 to 160° C. and maintained for 5 to 20 minutes to obtain a lead iodide thin film;
[0016] S6. Preparation of perovskite layer:
[0017] Dissolving methylammonium iodide in N,N-dimethylformamide, wherein the concentration of the methylammonium iodide is 5 to 12 mg / mL, to obtain a methylammonium iodide solution;
[0018] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 60 to 180° C. for 5 to 20 minutes to obtain a perovskite layer.
[0019] Preferably, the freezing device is a directional freezer.
[0020] Preferably, the aerogel template obtained in S104 is modified, and the modification comprises the following steps:
[0021] Spraying the modifying liquid onto the aerogel template and maintaining the modified liquid for 0.2 to 3 hours to obtain a modified aerogel template, wherein the mass volume ratio of the aerogel template to the modifying liquid is 1:2 to 1:5, and the modifying liquid is 1 to 5 wt% of 3-aminopropyltriethoxysilane or 0.05 mol / L of acetic acid solution;
[0022] The modified aerogel template is washed with deionized water and dried at 25 to 60° C. for 1 to 3 hours to obtain a modified aerogel template.
[0023] Preferably, the substrate is FTO glass or ITO glass.
[0024] In a second aspect, a perovskite layer is provided, which is prepared by any of the above-described two-step coating methods for preparing a perovskite layer.
[0025] In a third aspect, a photovoltaic module is provided, comprising a perovskite layer prepared by any of the two-step coating methods as described above, or a perovskite layer as described above.
[0026] The beneficial effects of the technical solution provided by this application include:
[0027] The embodiment of the present application provides a method for preparing a perovskite layer by a two-step coating method, a perovskite layer and a photovoltaic module, wherein an aerogel template is mixed with a precursor solution, and the pore structure of the aerogel template provides a growth template for perovskite crystals, guiding the crystals to grow directional in the pores, thereby improving the uniformity of crystallinity, reducing the number of grain boundary defects and charge recombination centers, and further improving the photoelectric performance of the film; and the rich pore structure of the aerogel template can improve the wettability of the precursor solution on the substrate, so that the precursor solution is more evenly spread on the substrate, which is conducive to the uniform growth of subsequent perovskite crystals, so as to improve the light absorption efficiency and charge transfer efficiency, and further improve the photoelectric performance of the film;
[0028] Ammonium fluoride is added during the preparation of the precursor solution. On the one hand, ammonium fluoride promotes the crystallization process of the perovskite film and improves the crystallinity and uniformity of the film. On the other hand, it can react with the hydroxyl groups on the surface of the electron transport layer (such as tin dioxide, titanium dioxide, etc.) below the perovskite layer, remove the hydroxyl groups in the form of water, and replace them with fluoride ions. This process helps to eliminate the hydroxyl groups at the interface, reduce interface defects, and thus improve interface properties. Therefore, it can solve the problem of poor crystallinity and uniformity of the perovskite layer prepared by the two-step method in the related art. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 A flow chart of a method for preparing a perovskite layer by a two-step coating method provided in this application;
[0031] Figure 2 A flow chart for preparing aerogel templates provided for this application. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0033] The present application provides a method for preparing a perovskite layer by a two-step coating method, a perovskite layer and a photovoltaic module, which can solve the problem of poor crystallinity and uniformity of the perovskite layer prepared by the two-step method in the related art. The method comprises the following steps:
[0034] S1. Providing aerogel template:
[0035] S101, mixing 99% tetraethyl silicate (TEOS) and anhydrous ethanol in a volume ratio of 1:5 to 1:10, adding deionized water and 1 mol / L hydrochloric acid solution, stirring evenly to obtain a sol, wherein the volume ratio of tetraethyl silicate to deionized water is 1:1 to 1:10, and the volume ratio of the hydrochloric acid solution to the tetraethyl silicate is 1:100;
[0036] S102, placing the sol in a sealed container, stirring at 50-65° C. for hydrolysis and polycondensation reaction to obtain a wet gel; TEOS is hydrolyzed under acid catalysis to generate silicic acid, and then silicic acid molecules and silicic acid and TEOS molecules undergo polycondensation reaction to form a wet gel with a three-dimensional network structure.
[0037] S103, placing the wet gel in a freezing device, starting freezing at 25°C, cooling at a constant rate to -80°C, and keeping for 5 to 30 minutes to obtain a frozen gel, the freezing rate being 0.5 to 5°C / min, wherein the freezing device can be an ultra-low temperature refrigerator.
[0038] By controlling the freezing rate, tiny ice crystals are formed in the wet gel, thus obtaining a void structure; a faster freezing rate helps to form even finer ice crystals, thus obtaining a finer porous structure.
[0039] In some embodiments, the freezing device is a directional freezer to control the freezing direction and guide the growth direction of ice crystals, thereby preparing an aerogel template with a specific arranged pore structure; specifically, a parallel plate directional freezing device can be used, which consists of two parallel metal plates, and the wet gel is placed between the two plates. By controlling the temperature of the two plates (usually one is cooled and the other is used as a heat sink or kept at room temperature), a temperature gradient is formed inside the sample, thereby guiding the ice crystals to grow in a direction parallel to the plate surface.
[0040] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature is uniformly raised from -60 to -50 ° C to 20 ° C, and the heating process is maintained for 3 to 8 hours to obtain an aerogel template; the frozen gel is placed in a vacuum drying oven and slowly heated at low temperature to allow the ice crystals to directly sublimate into water vapor and be discharged, thereby obtaining a porous aerogel template.
[0041] The nanoporous structure of the aerogel can serve as a template for the growth of perovskite crystals, guiding the directional growth of the crystals in the pores and promoting the formation of a more uniform precursor film, thereby improving the uniformity of crystallinity.
[0042] In some embodiments, after S104, the following steps are further included:
[0043] The aerogel template obtained in S104 is modified, and the modification comprises the following steps:
[0044] Spraying the modifying liquid onto the aerogel template and maintaining the modified liquid for 0.2 to 3 hours to obtain a modified aerogel template, wherein the mass volume ratio of the aerogel template to the modifying liquid is 1:2 to 1:5, and the modifying liquid is 1 to 5 wt% of 3-aminopropyltriethoxysilane or 0.05 mol / L of acetic acid solution;
[0045] The modified aerogel template is washed with deionized water and dried at 25 to 60° C. for 1 to 3 hours to obtain a modified aerogel template.
[0046] By modifying the aerogel template, the compatibility of the aerogel template and the precursor solution is enhanced; when 3-aminopropyltriethoxysilane (APTES) is used as a modifier, the aerogel template is a SiO2 aerogel template, and the ethoxy groups of APTES form silanols after hydrolysis, which can undergo condensation reactions with the hydroxyl groups on the surface of the SiO2 aerogel template to form covalent bonds and introduce amino functional groups. The amino functional groups are exposed on the template surface, providing favorable nucleation sites for subsequent perovskite deposition, thereby improving the adhesion and crystallinity of the perovskite film on the template, thereby improving the photoelectric properties of the perovskite film and improving the charge transfer efficiency.
[0047] When acetic acid is used as a modifier, as an organic acid, its carboxyl group can react with the hydroxyl group on the surface of the aerogel template, change the chemical properties of the aerogel template, reduce the dangling bonds on the template surface, improve the crystallinity and stability of the template, and help the uniform distribution and penetration of the precursor solution, thereby forming a high-quality perovskite film.
[0048] S2. Prepare a precursor solution: mix 0.1 mol / L lead acetate and 0.1 mol / L potassium iodide in a volume ratio of 1:3 to 1:5, and add ammonium fluoride to obtain a precursor solution, wherein the molar ratio of ammonium fluoride to lead acetate is 1:20 to 1:100;
[0049] The addition of ammonium fluoride can promote the crystallization process of perovskite films, improve the crystallinity and crystal uniformity of the films, help reduce defects in the films, and improve the quality of the films.
[0050] S3, preparing an aerogel-precursor solution: dispersing the aerogel template into the precursor solution at a mass volume ratio of 1:50 to 1:80, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0051] S4, preparing a precursor film: spin-coating the aerogel-precursor solution onto a substrate to form a precursor film; the substrate is FTO glass or ITO glass.
[0052] S5. First annealing treatment to prepare a lead iodide film: heat treatment is performed at 50 to 160° C. and maintained for 5 to 20 minutes to obtain a lead iodide film. The annealing treatment promotes the volatilization of the solvent in the precursor solution and the decomposition of organic matter, while promoting the formation and growth of perovskite crystals along the pore direction of the aerogel template.
[0053] S6. Preparation of perovskite layer:
[0054] Dissolving methylammonium iodide in N,N-dimethylformamide, wherein the concentration of the methylammonium iodide is 5 to 12 mg / mL, to obtain a methylammonium iodide solution;
[0055] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 60 to 180° C. for 5 to 20 minutes to obtain a perovskite layer.
[0056] Example 1
[0057] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0058] S1. Providing aerogel template:
[0059] S101, mixing 10 mL of 99% tetraethyl orthosilicate (TEOS) with 50 mL of anhydrous ethanol, and then adding 10 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution and stirring evenly to obtain a sol;
[0060] S102, placing the sol in a sealed container, stirring at 50° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0061] S103, placing the wet gel in an ultra-low temperature freezer, starting freezing at 25°C, cooling to -80°C at a freezing rate of 0.5°C / min, and keeping at -80°C for 5 minutes to obtain a frozen gel;
[0062] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature is uniformly raised from -60°C to 20°C, and the heating process is maintained for 4 hours to obtain an aerogel template;
[0063] S2. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 600 mL of 0.1 mol / L potassium iodide, and add 0.037 g of ammonium fluoride thereto to obtain a precursor solution;
[0064] S3, preparing an aerogel-precursor solution: dispersing 10 g of an aerogel template into 500 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0065] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the FTO glass to form a precursor film;
[0066] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 50° C. and maintained for 20 minutes to obtain a lead iodide thin film;
[0067] S6. Preparation of perovskite layer:
[0068] Dissolve 500 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain a 5 mg / mL methylammonium iodide solution;
[0069] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 60° C. for 20 minutes to obtain a perovskite layer.
[0070] Example 2
[0071] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0072] S1. Providing aerogel template:
[0073] S101, 10 mL of 99% tetraethyl orthosilicate (TEOS) was mixed with 100 mL of anhydrous ethanol, and then 100 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution were added and stirred to obtain a sol;
[0074] S102, placing the sol in a sealed container, stirring at 60° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0075] S103, placing the wet gel in a parallel plate directional freezing device, starting freezing at 25°C, cooling to -80°C at a freezing rate of 2°C / min, and keeping at -80°C for 10 min to obtain a frozen gel;
[0076] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature was uniformly raised from -50°C to 20°C, and the heating process was maintained for 7h to obtain an aerogel template;
[0077] S2. Prepare a precursor solution: mix 100 mL of 0.1 mol / L lead acetate and 500 mL of 0.1 mol / L potassium iodide, and add 0.0148 g of ammonium fluoride thereto to obtain a precursor solution;
[0078] S3, preparing an aerogel-precursor solution: dispersing 6 g of an aerogel template into 480 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0079] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the FTO glass to form a precursor film;
[0080] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 160° C. and maintained for 5 minutes to obtain a lead iodide thin film;
[0081] S6. Preparation of perovskite layer:
[0082] Dissolve 1200 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain a 12 mg / mL methylammonium iodide solution;
[0083] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 180° C. for 5 minutes to obtain a perovskite layer.
[0084] Example 3
[0085] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0086] S1. Providing aerogel template:
[0087] S101, 10 mL of 99% tetraethyl orthosilicate (TEOS) was mixed with 70 mL of anhydrous ethanol, and then 30 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution were added and stirred to obtain a sol;
[0088] S102, placing the sol in a sealed container, stirring at 55° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0089] S103, placing the wet gel in a parallel plate directional freezing device, starting freezing at 25°C, cooling to -80°C at a freezing rate of 3°C / min, and keeping at -80°C for 15 minutes to obtain a frozen gel;
[0090] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature was uniformly raised from -55°C to 20°C, and the heating process was maintained for 6 hours to obtain an aerogel template;
[0091] The aerogel template is modified:
[0092] Spray 20 mL of 1 wt % 3-aminopropyltriethoxysilane onto 10 g of the aerogel template and keep it for 3 h to obtain a modified aerogel template;
[0093] The modified aerogel template was washed with deionized water and dried at 25° C. for 1 h to obtain a modified aerogel template.
[0094] S2. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 800 mL of 0.1 mol / L potassium iodide, and add 0.0185 g of ammonium fluoride thereto to obtain a precursor solution;
[0095] S3, preparing an aerogel-precursor solution: dispersing 10 g of an aerogel template into 600 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0096] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the ITO glass to form a precursor film;
[0097] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 100° C. and maintained for 15 minutes to obtain a lead iodide thin film;
[0098] S6. Preparation of perovskite layer:
[0099] Dissolve 800 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain an 8 mg / mL methylammonium iodide solution;
[0100] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 140° C. for 12 minutes to obtain a perovskite layer.
[0101] Example 4
[0102] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0103] S1. Providing aerogel template:
[0104] S101, mixing 10 mL of 99% tetraethyl orthosilicate (TEOS) with 80 mL of anhydrous ethanol, and then adding 50 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution and stirring evenly to obtain a sol;
[0105] S102, placing the sol in a sealed container, stirring at 60° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0106] S103, placing the wet gel in a parallel plate directional freezing device, starting freezing at 25°C, cooling to -80°C at a freezing rate of 2°C / min, and keeping at -80°C for 15 minutes to obtain a frozen gel;
[0107] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature was uniformly raised from -55°C to 20°C, and the heating process was maintained for 7h to obtain an aerogel template;
[0108] The aerogel template is modified:
[0109] Spray 30 mL of 5 wt % 3-aminopropyltriethoxysilane onto 10 g of the aerogel template and keep it for 0.5 h to obtain a modified aerogel template;
[0110] The modified aerogel template was washed with deionized water and dried at 35° C. for 2 h to obtain a modified aerogel template.
[0111] S2. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 800 mL of 0.1 mol / L potassium iodide, and add 0.0185 g of ammonium fluoride thereto to obtain a precursor solution;
[0112] S3, preparing an aerogel-precursor solution: dispersing 10 g of an aerogel template into 600 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0113] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the ITO glass to form a precursor film;
[0114] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 90° C. and maintained for 15 minutes to obtain a lead iodide thin film;
[0115] S6. Preparation of perovskite layer:
[0116] Dissolve 800 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain an 8 mg / mL methylammonium iodide solution;
[0117] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 140° C. for 12 minutes to obtain a perovskite layer.
[0118] Example 5
[0119] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0120] S1. Providing aerogel template:
[0121] S101, 10 mL of 99% tetraethyl orthosilicate (TEOS) was mixed with 80 mL of anhydrous ethanol, and then 70 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution were added and stirred to obtain a sol;
[0122] S102, placing the sol in a sealed container, stirring at 65° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0123] S103, placing the wet gel in a parallel plate directional freezing device, starting freezing at 25°C, cooling to -80°C at a freezing rate of 1°C / min, and keeping at -80°C for 30 minutes to obtain a frozen gel;
[0124] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature was uniformly raised from -55°C to 20°C, and the heating process was maintained for 8 hours to obtain an aerogel template;
[0125] The aerogel template is modified:
[0126] Spray 40 mL of 3 wt % 3-aminopropyltriethoxysilane onto 10 g of the aerogel template and keep it for 2 h to obtain a modified aerogel template;
[0127] The modified aerogel template was washed with deionized water and dried at 60° C. for 1 h to obtain a modified aerogel template.
[0128] S2. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 800 mL of 0.1 mol / L potassium iodide, and add 0.0185 g of ammonium fluoride thereto to obtain a precursor solution;
[0129] S3, preparing an aerogel-precursor solution: dispersing 10 g of an aerogel template into 600 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0130] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the ITO glass to form a precursor film;
[0131] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 120° C. and maintained for 12 minutes to obtain a lead iodide thin film;
[0132] S6. Preparation of perovskite layer:
[0133] Dissolve 800 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain an 8 mg / mL methylammonium iodide solution;
[0134] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 120° C. for 12 minutes to obtain a perovskite layer.
[0135] Example 6
[0136] The method for preparing a perovskite layer by a two-step coating method provided in this embodiment comprises the following steps:
[0137] S1. Providing aerogel template:
[0138] S101, mixing 10 mL of 99% tetraethyl orthosilicate (TEOS) with 80 mL of anhydrous ethanol, and then adding 50 mL of deionized water and 0.1 mL of 1 mol / L hydrochloric acid solution and stirring evenly to obtain a sol;
[0139] S102, placing the sol in a sealed container, stirring at 60° C. for hydrolysis and polycondensation reaction to obtain a wet gel;
[0140] S103, placing the wet gel in a parallel plate directional freezing device, starting freezing at 25°C, cooling to -80°C at a freezing rate of 5°C / min, and keeping at -80°C for 15 minutes to obtain a frozen gel;
[0141] S104, transferring the frozen gel to a vacuum dryer, reducing the pressure to 10 -3 Pa, the temperature was uniformly raised from -55°C to 20°C, and the heating process was maintained for 3 h to obtain an aerogel template;
[0142] The aerogel template is modified:
[0143] Spray 50 mL of 0.05 mol / L acetic acid onto 10 g of the aerogel template and keep it for 0.2 h to obtain a modified aerogel template;
[0144] The modified aerogel template was washed with deionized water and dried at 40° C. for 2 h to obtain a modified aerogel template.
[0145] S2. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 800 mL of 0.1 mol / L potassium iodide, and add 0.0185 g of ammonium fluoride thereto to obtain a precursor solution;
[0146] S3, preparing an aerogel-precursor solution: dispersing 10 g of an aerogel template into 600 mL of a precursor solution, stirring and ultrasonically treating to obtain an aerogel-precursor solution;
[0147] S4, preparing a precursor film: spin coating the aerogel-precursor solution onto the ITO glass to form a precursor film;
[0148] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 120° C. and maintained for 12 minutes to obtain a lead iodide thin film;
[0149] S6. Preparation of perovskite layer:
[0150] Dissolve 800 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain an 8 mg / mL methylammonium iodide solution;
[0151] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 120° C. for 12 minutes to obtain a perovskite layer.
[0152] Comparative Example 1
[0153] The method for preparing a perovskite layer by a two-step coating method provided in this comparative example comprises the following steps:
[0154] S1. Prepare a precursor solution: mix 200 mL of 0.1 mol / L lead acetate and 800 mL of 0.1 mol / L potassium iodide, and add 0.0185 g of ammonium fluoride thereto to obtain a precursor solution;
[0155] S2, preparing a precursor film: spin coating the precursor solution onto the ITO glass to form a precursor film;
[0156] S5, a first annealing treatment to prepare a lead iodide thin film: heat treatment is performed at 120° C. and maintained for 12 minutes to obtain a lead iodide thin film;
[0157] S6. Preparation of perovskite layer:
[0158] Dissolve 800 mg of methylammonium iodide in 100 mL of N,N-dimethylformamide to obtain an 8 mg / mL methylammonium iodide solution;
[0159] The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 120° C. for 12 minutes to obtain a perovskite layer.
[0160] Comparative Example 2
[0161] The method for preparing a perovskite layer by a two-step coating method provided in this comparative example is different from that in Example 4 in that no hydrochloric acid solution is added in step S1 and no ammonium fluoride is added in step S2.
[0162] Comparative Example 3
[0163] The method for preparing a perovskite layer by a two-step coating method provided in this comparative example is different from that in Example 4 in that, in step S103, an ultra-low temperature refrigerator is used as a freezing device.
[0164] Specifically, the comparison of raw material input in the preparation methods of Examples 1 to 6 and Comparative Examples 1 to 3 is shown in Table 1.
[0165] Table 1 Raw material input in the preparation method of Example 1 to Example 6
[0166]
[0167] Table 2 Raw material input in the preparation method of Comparative Examples 1 to 3
[0168]
[0169] The present application also provides a perovskite layer, which is prepared by the methods of the above embodiments 1 to 6.
[0170] On the other hand, the present application also provides a photovoltaic module prepared by using the perovskite layer prepared in the above embodiment, specifically a prepared solar cell. Specifically, the solar cell includes a transparent conductive layer (TCO), an electron transport layer (ETL), a perovskite light absorption layer, a hole transport layer (HTL) and a metal electrode arranged in sequence, wherein the transparent conductive layer is fluorine-doped tin oxide with a thickness of 200nm, the electron transport layer is titanium dioxide with a thickness of 25nm, the perovskite light absorption layer is the perovskite layer prepared in the above embodiments 1 to 6 and comparative examples 1 to 3, and its thickness is 500nm, the hole transport layer is nickel oxide with a thickness of 50nm, and the metal electrode is silver (Ag) with a thickness of 80nm.
[0171] The solar cell was tested for performance by using a solar simulator and an IV tester (current-voltage tester) to measure the current-voltage (IV) curve of the solar cell under simulated standard solar illumination conditions:
[0172] Place the solar cell in a temperature control box and set the temperature to 25°C;
[0173] A solar simulator was used to provide standard lighting conditions (light intensity of 1000 W / m 2 , AM 1.5G spectrum);
[0174] Connect the IV tester and solar cell to ensure the circuit connection is correct;
[0175] Under standard test conditions, the solar cell is scanned using an IV tester to obtain a current-voltage (IV) curve;
[0176] The open circuit voltage (VOC), short circuit current density (JSC) and fill factor (FF) are calculated from the IV curve to obtain the photoelectric conversion efficiency (PCE); the higher the PCE value, the better the photoelectric conversion performance of the solar cell. Specifically, the photoelectric conversion efficiency (PCE) of the solar cells made of the perovskite layers prepared in Examples 1 to 6 and Comparative Examples 1 to 3 is shown in Table 3.
[0177] Table 3
[0178] Photoelectric conversion efficiency / % Example 1 20.65 Example 2 23.12 Example 3 25.96 Example 4 26.33 Example 5 25.50 Example 6 25.41 Comparative Example 1 11.23 Comparative Example 2 18.03 Comparative Example 3 21.46
[0179] It can be known that the solar cells prepared by the perovskite layers of Examples 3 to 6 have a higher photoelectric conversion efficiency, that is, after the aerogel template is directionally frozen at a certain cooling rate, a growth template with a rich pore structure is formed, in which the perovskite crystals grown can grow directionally to form a more uniform crystal, thereby obtaining a more uniform precursor film, further improving the interface interaction between the film and the substrate, enhancing the adhesion of the film, improving its stability, reducing the number of grain boundary defects and charge recombination centers, and thus improving the photoelectric performance of the film; and after the aerogel template is modified, its photoelectric conversion efficiency is further improved, indicating that the organic functional groups introduced by the modification enhance the interaction between the aerogel template and the precursor solution, improve the template effect, and thus improve the photoelectric conversion efficiency of the battery.
[0180] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a perovskite layer by a two-step coating method, characterized in that: It includes the following steps: S1. Provide aerogel template: S101, mixing 99% ethyl silicate and anhydrous ethanol in a volume ratio of 1:5 to 1:10, adding deionized water and 1 mol / L hydrochloric acid solution, and stirring uniformly to obtain a sol, wherein the volume ratio of the ethyl silicate to the deionized water is 1:1 to 1:10, and the volume ratio of the hydrochloric acid solution to the ethyl silicate is 1:100; S102, placing the sol in a sealed container, stirring at 50-65° C. for hydrolysis and polycondensation reaction to obtain a wet gel; S103, placing the wet gel in a freezing device, starting from 25°C and cooling at a constant rate to -80°C, stopping, and maintaining for 5 to 30 minutes to obtain a frozen gel, with a freezing rate of 0.5 to 5°C / min; S104, transferring the frozen gel to a vacuum desiccator, reducing the pressure to 10 -3 Pa, the temperature is uniformly raised from -60 to -50 ° C to 20 ° C, and the heating process is maintained for 3 to 8 hours to obtain an aerogel template; S2. Preparing a precursor solution: mixing 0.1 mol / L lead acetate and 0.1 mol / L potassium iodide in a volume ratio of 1:3 to 1:5, and adding ammonium fluoride to obtain a precursor solution, wherein the molar ratio of ammonium fluoride to lead acetate is 1:20 to 1:50; S3, preparing an aerogel-precursor solution: dispersing the aerogel template into the precursor solution at a mass-to-volume ratio of 1:50 to 1:80, stirring and ultrasonically treating to obtain an aerogel-precursor solution; S4, preparing a precursor film: spin-coating the aerogel-precursor solution onto a substrate to form a precursor film; S5, a first annealing treatment to prepare a lead iodide thin film: performing a heat treatment at 50-160° C. and maintaining it for 5-20 minutes to obtain a lead iodide thin film; S6. Preparation of perovskite layer: dissolving methylammonium iodide in N,N-dimethylformamide, wherein the concentration of the methylammonium iodide is 5 to 12 mg / mL, to obtain a methylammonium iodide solution; The methylammonium iodide solution is coated on the lead iodide film, and a second annealing treatment is performed at 60 to 180° C. for 5 to 20 minutes to obtain a perovskite layer.
2. The method for preparing a perovskite layer by a two-step coating method according to claim 1, wherein: The freezing device is a directional freezer.
3. The method for preparing a perovskite layer by a two-step coating method according to claim 1, wherein: It also includes: The aerogel template obtained in S104 is modified, and the modification comprises the following steps: Spraying the modifying liquid onto the aerogel template and maintaining it for 0.2 to 3 hours to obtain a modified aerogel template, wherein the mass volume ratio of the aerogel template to the modifying liquid is 1:2 to 1:5, and the modifying liquid is 1 to 5 wt% 3-aminopropyltriethoxysilane or 0.05 mol / L acetic acid solution; The modified aerogel template is washed with deionized water and dried at 25-60° C. for 1-3 hours to obtain a modified aerogel template.
4. The method for preparing a perovskite layer by a two-step coating method according to claim 1, wherein: The substrate is FTO glass or ITO glass.
5. A perovskite layer, characterized in that The perovskite layer is prepared by the two-step coating method according to any one of claims 1 to 4.
6. A photovoltaic module, characterized in that: It comprises the perovskite layer according to claim 5.
